Cross‐Coupling of Allenamides and C‐Based Nucleophiles by Pd‐Catalyzed Allylic Alkylation. Issue 5 (22nd December 2020) - Sieber, Joshua D.; Klake, Raphael K.; Agrawal, Toolika; Ho, Dang Binh; Gargaro, Samantha L.; Collins, Stephen; Edwards, Mytia D.
Abstract: Pd‐catalyzed allylic alkylation of C ‐based nucleophiles using both chiral and achiral allenamides is described. High yields were obtained to provide synthetically valuable ( E )‐enamide products in high E : Z ‐selectivity while generating a quaternary carbon atom. Some potential stereocontrolled applications of the resultant ( E )‐enamide functionality are described. Abstract :